A Via Campesina Brasil e a avaliação da primeira década de impactos da reforma agrária do Banco Mundial - Ramos Filho, Eraldo da Silva [UNESP] (Univ Barcelona, Dept Geografia Humana, 2008)
During the past decade, influenced strongly by World Bank land policies, many governments instituted a new mode of recreating the peasantry, one supposedly led by market forces through credit programs secured by land. Supported by large landowner organizations, defended as a conquest by the rural labor movement and combated by member organizations of the Via Campesina, the new mode of peasant renovation has inspired a diversity of interpretations both positive and negative. To evaluate these events, this article seeks to demonstrate the World Bank's intentionality in urging the implementation of market-led agrarian reform in developing countries; discusses the construction of immaterial territories in the context of this policy; analyzes the development of a people's think tank in response to the agitation of the Via Campesina Brazil and the negative impact of the credit system on peasants.
An evaluation of the first decade of the World Bank's market-based agrarian reform project and the Via Campesina Brazil
Keywords: agrarian question; agrarian reform; neoliberalismo; territorialization; Think tanks